ANTHOCYANIN-CONTAINING PLANT EXTRACTS AS AN ALTERNATIVE DYE FOR MICROSCOPIC EXAMINATION OF SOIL-TRANSMITTED HELMINTHS - Ari Nuswantoro; Riska Alfianita; Fitra Fathuhudin; Veny Veny (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Eosin is commonly used for microscopic examination of Soil-Transmitted Helminth (STH) infections, but natural anthocyanin-based pigments remain underutilized. Purpose: This study evaluates the potential of anthocyanins extracted from red beans (Phaseolus vulgaris), hibiscus flowers (Hibiscus rosa-sinensis), and amaranth leaves (Amaranthus tricolor) as eosin alternatives for staining STH eggs in stool smears. Method: Extracts were obtained using 96% ethanol for 24, 48, and 72 hours, with nine replications. Stool preparations were stained with these extracts and compared to eosin, assessing color intensity, contrast, and egg layer clarity. Result: Red bean extracts scored 2.1, 2.7, and 2.8 at 24, 48, and 72 hours, with the latter two showing no significant difference from eosin. Hibiscus flower extracts scored 1.6, 2.2, and 2.8, with the 72 hours extract comparable to eosin. Amaranth leaf extracts scored 1.4, 1.7, and 1.9, all significantly different from eosin. Conclusion: Red bean extracts (48 and 72 hours) and hibiscus flower extract (72 hours) provided staining comparable to eosin, with red bean extract being the most promising alternative. These findings suggest that anthocyanin-based stains can serve as viable substitutes for eosin in diagnosing helminthiasis via stool smear microscopy.